Elucidating membrane proteomic responses of Escherichia coli to alcohol stress - Sen, Oishi (Nanyang Technological University, 2022)
Bioalcohol is a renewable and environment-friendly alternative to present day fossil fuels, which are non-renewable and greenhouse gas emitters. However, alcohol toxicity to microbial cells is the limiting factor to profitable, large-scale production of alcohol by fermentation. An in-depth understanding of how the bacterial cells respond to alcohol stress by altering its membrane proteome can provide valuable information, which might be useful in improving microbial tolerance to alcohol and hence enable large scale production. The current study deals with the understanding of changes in the membrane protein composition of Escherichia coli in the presence of ethanol, butanol and hexanol. Further, the study focusses on confirming the changes in the expression of important outer membrane proteins under alcohol stress and predict the effect of such response on the functional integrity of the outer membrane.